Nanoporous FeP nanorods grown on Ti plate as an enhanced binder-free hydrogen evolution cathode. (6th February 2017) - Gao, J J; Luo, P; Qiu, H-J; Wang, Y
Abstract: A porous and interconnected nanorod-like FeP structure on titanium plate has been fabricated by a simple hydrothermal method and followed by a calcination process. The nanorod is assembled by many paralleled FeP nanowires with a porous structure. With the porous surface structure of FeP nanorods and the synergetic effect from the electronic conductive Ti support, this binder-free FeP electrode brings about a desirable electrocatalytic activity for the hydrogen evolution reaction (HER), showing a low onset overpotential of 23 mV and a small Tafel slope of 39 mV dec −1 . Meanwhile, its catalytic activity could be maintained almost unchanged for at least 12 h in an acidic solution. This work provides us an effective HER electrocatalyst which can be easily produced on a large scale and at low cost.